An Assessment of the Benefits of Online Scenario Simulation Tools in Homeland Security and Emergency Management Education - Renda-Tanali, Irmak; Abdul-Hamid, Husein (Journal of homeland security and emergency management, 2011)
In this paper, online scenario simulations were examined. The results show that there is an association between students satisfaction with the tools and the grade in the course. These tools add value to understanding the subject matter and provide students with near real-life hands-on experience.